Characterization of polycyclic aromatic hydrocarbons in soil in a coal mining area, East China: Spatial distribution, sources, and carcinogenic risk assessment - Ren, Mengxi; Zheng, Liugen; Hu, Jie; Chen, Xing; Zhang, Yanhai; Dong, Xianglin; Wei, Xiangping; Cheng, Hua (Frontiers in Earth Science, 2022)
The polycyclic aromatic hydrocarbon (PAH) pollution process in mining areas, particularly coal mining areas, has accelerated because of coal chemical production and gangue accumulation. We characterized and analyzed PHAs in surface soil using gas chromatography–mass spectrometry, analyzed sources using diagnostic binary ratios and positive matrix factorization, assessed the associated potential carcinogenic risks using Monte Carlo method. Our results showed a wide PAH concentration range (218–1548 ng g-1). The high molecular weight proportion in contaminated areas increased significantly (25%), being 10% higher than in uncontaminated areas. Clear differences in PAH distribution were detected in contaminated areas, with higher concentrations in the soils near an industrial park and coal gangue piles. Factorization of a positive definite matrix showed the high contribution rate of coking in contaminated areas. In contrast with the 10% contribution rate of the coking source in uncontaminated areas, the rate in contaminated areas was 31%. The Monte Carlo method was used to assess the cancer risk to residents in the study areas. The carcinogenic health risk values for adults in contaminated areas at 95% confidence levels is slightly higher than the safety standard (2.92×10-6) prescribed by the United States Environmental Protection Agency. Sensitivity analysis showed that the relative exposure duration (ED) and soil surface area of skin exposure were the most significant parameters for adults, and ED and body weight for children. Notably, in contaminated areas, the cancer risk was five times higher for both adults and children than in uncontaminated areas.